2015
DOI: 10.12738/estp.2015.5.0071
|View full text |Cite
|
Sign up to set email alerts
|

Social Studies in Improving Students’ Map Skills: Teachers’ Opinions

Abstract: Teaching skills is one of the building blocks of Turkey's Social Studies Instructional Program. Via skills, information can be effectively transformed into high-level behaviors, that information may become a part of one's daily life, and that one may make right decisions concerning major issues in his/her life. Map skills are called "spatial perception skills" within Turkey's Social Studies Instructional Program. Map skills-one of the basic geographical skills-can easily be employed by students to solve a wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
1
3
0
1
Order By: Relevance
“…This result is also in line with the literature which shows a relationship between map use and map literacy (Aksoy & Ablak, 2019). In contrast, it is known that material infrastructure, such as maps, is insufficient for learning due to students' weak mapping skills (Gökçe, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…This result is also in line with the literature which shows a relationship between map use and map literacy (Aksoy & Ablak, 2019). In contrast, it is known that material infrastructure, such as maps, is insufficient for learning due to students' weak mapping skills (Gökçe, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Theoretical analysis of teaching practices has shown that only when the teacher constantly use maps during the geography lessons, pupils are more successful in understanding cartographic concepts, however, the influence of different methods and techniques on students' cartographic skills should be further determined (Gökçe 2015). Only deliberate and systematic work on the formation of methods of map reading the map leads to the acquisition of cartographic competence and develops pupils cognitive activity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a teacher can use interactive crossword puzzles or interactive maps where pupils move one finger in continental space and use it during testing, such as in a test mode. In-service training programs should be conducted in order to help teachers catch up on skills in preparing and using maps and in technologies, such as GIS, Google Earth, and Google Map (Gökçe 2015). These technologies are powerful tools in this work as they provide high visibility of displaying diverse information in the form of interactive electronic maps.…”
Section: Discussionmentioning
confidence: 99%
“…En la enseñanza de la Historia, y especialmente de la Geografía, los mapas son fundamentales, y así se consideran desde hace décadas (Fairgrieve, 1932), pero para ello estos han de contener información muy precisa, visual, limpia, despertar interés y además ofrecer explicaciones (Sancho, 1996). A pesar de que a priori se pueda pensar que a las edades de los participantes los mapas son superfluos, recientes investigaciones (Dijk, Schee, Trimp & Zijpp, 1994;Gökçe, 2016;Piñeiro & Melón, 2002) aportan datos clarificadores sobre las serias dificultades que los estudiantes tienen a la hora de trabajar con mapas o ubicar determinados elementos geográficos en el espacio.…”
Section: Discussionunclassified